Overview of the Level of Knowledge of Narisa Pharmacy Consumers Against Cough Self-Medication - Herman, Herman; Roosevelt, Alfreds; Kasman, Umrah (Jurnal Farmasi Sandi Karsa, 2022)
Self-medication is an effort that most people make to deal with complaints or symptoms of disease before they decide to seek help at a health service center/health worker. Coughing is a reflection that is aroused by irritation of the lungs or respiratory tract. This study aims to describe the level of knowledge of Narisa pharmacy consumers on cough self-medication. This research was conducted from September to November 2022 at the Narisa Pharmacy. This type of research uses a descriptive method using a questionnaire. With a total sample of 88 respondents, the sample was taken using a non-probability sampling technique, namely accidental sampling. The results of this study indicate that the percentage results are 93.58%. Based on the results of the percentage of respondents' answers, it can be concluded that the level of knowledge of Narisa pharmacy consumers is categorized as high level of knowledge.